D06 Quantitative assays to monitor huntingtin changes in pre-clinical and clinical hd samples. (September 2018) - Kuhlbrodt, Kirsten; Baldo, Barbara; Reindl, Wolfgang; Carty, Nikisha; Tillack, Karsten; Berson, Nadege; Mack, Volker; Bazenet, Chantal; Herrmann, Frank; vanderKam, Elizabeth; Bard, Jonathan; Munoz-Sanjuan, Ignacio; et al.
Abstract : Background: Huntington's disease (HD) is a progressive neurodegenerative disease caused by a polyglutamine repeat expansion in the huntingtin (HTT) protein with no effective disease-modifying therapies available. Mutant HTT toxicity, associated with the misfolding of the expanded polyglutamine repeat-containing protein, affects several intracellular pathways and leads to widespread neurodegeneration. In addition, mutant HTT forms intracellular aggregates, which contribute to disease pathogenesis. One promising strategy to develop HD modifying therapies aim to repress or reduce the amount of mutant HTT expression and aggregation. However, in order to monitor the efficacy of such approaches there is the need for robust and reliable immunoassays that are able to quantitate mutant HTT in biological samples. Aims: To develop immunoassays and high content histological approaches able to quantify and monitor changes in soluble HTT levels as well as in HTT aggregates in different biological samples. Methods: Meso Scale Discovery (MSD), TR-FRET and Millipore Erenna platforms were used to develop several immunoassays to measure soluble and aggregated mutant HTT. High-content histological approaches using the Opera platforms in combination with image analysis algorithms were optimized to quantify mutant HTT inclusions. Results: We have established and validated sensitive and robust immunoassays to be able to measure soluble and aggregated HTT levels in pre-clinical and clinical biological samples. Using the Millipore Erenna platform, we can also reliably quantify mutant HTT in cerebrospinal fluid from HD patients. Finally, a combination of high content histological analysis with custom adaptations of image analysis algorithms allows us to perform quantitation of spatial and temporal changes in HTT inclusions in tissues from HD animal models. Conclusions: We have established a wide portfolio of immunoassays and imaging tools able to investigate changes in HTT levels and aggregation as well as monitor disease progression in pre-clinical and clinical samples, including assessment of CSF mutant HTT levels. These assays are valuable tools to support the therapeutic approaches aimed to lower HTT expression.